Political demand making and self-efficiency among Aetas in Lip-lip resettlement area - Antonio, Harold M.; Anicete, Jocelyn; Bucle, Erizza Dawn (2001)
This study puts into light the demand-making practices of he Aeta culture following the eruption of Mt. Pinatubo in 1990. The significance of the time frame mentioned is owed to the fact that prior to the eruption of Mt. Pinatubo, the Aetas lived in isolation, enjoying an apolitical way of life. Four modes of demand making were ope-rationalized in the study. The first two were Formal and Informal, with the former measured in terms of frequency of attendance in Barangay meetings vis-a-vis the frequency of presentation of demands made by one; and latter determined in terms of frequency of contacts by the respondents with their barangay officials with reference to the suggestions rendered to the officers outside of barangay meetings. The third mode, demand making on other Government organizations, was indicated by the frequency by which they forwarded their concerns to specific government organizations. And the fourth mode, demand making on social or civic organizations, included the frequency of contacts made to non-government agencies. The target field of study was the Camias Resettlement area, particularly sitiu Liplip of Porac Pampanga. Purposive sampling was used in the research, with thirty respondents, all males, comprising the representative population. Survey interview, lasting for about 25-30 minutes as administered individually, was the primary technique employed in the collection of data. The result of the research showed that: the residents of Liplip possess high awareness regarding the formal meetings held in their community. There is a high rate of attendance in these meetings by the Aeta of Liplip. There exists a high correlation between the high frequency of attendance and their high sense of self-efficacy as manifested by their high tendency to voice out their demands during formal or informal meetings. The Aeta people remain dedicated in attending and cooperating during community meetings despite the fact that most of their demands remain nebulous. That there is no correlation between perception of low level of responsiveness on the part of the community leaders and the respondents' tendency to attend meetings and make suggestions during gatherings -- Author's abstract.
Thesis (Bachelor of Arts in Social Sciences) -- University of the Philippines Baguio, 2001.
Includes bibliographical references.
Keywords: Aeta (Philippine people) -- Philippines -- Lip-lip (Pampanga).; Political participation -- Philippines -- Lip-lip (Pampanga).